Annular Lichenoid Dermatitis (of Youth) Immunohistochemical and Serological Evidence for Another Clinical Presentation of Borrelia Infection in Patients of Western Austria. (March 2017) - Wilk, Michael; Zelger, Bettina G.; Emberger, Michael; Zelger, Bernhard
Abstract : Abstract: Annular lichenoid dermatitis of youth (ALDY) is a more recently described inflammatory disease of the skin of unknown etiology with clinical similarities to morphea. The authors clinically, histopathologically, and immunohistochemically investigated 14 biopsies from 12 patients in western Austria with this disease. There were 6 female and 6 male patients with solitary (n = 7) and multiple lesions (n = 5) affecting the trunk (n = 11), upper arm (n = 2), thigh (n = 1), and calf (n = 1). Clinically, early lesions were erythematous in nature leading to central paleness, scaling, wrinkling, dermal atrophy, slight pigmentation, and telangiectasia later on. Histopathologically, all specimens showed the typical features of ALDY with a superficial lichenoid process with sprinkling of lymphocytes along the basal cell layer and within the epidermis accompanied by mild fibrosis. Pigment incontinence, superficial fibrosis, and dilatation of superficial capillary vessels are prominent features in more advanced stages of disease. Immunohistologically, using a polyclonal antibody against Borrelia, 11/14 specimens revealed spirochetes, either vital (n = 4) or degenerated (n = 7), in close proximity to collagen bundles. Thirteen of 14 specimens in addition showed focal (n = 4) or clustered (n = 9) positivity for CD20 in the papillary dermis. Nine of 12 sera tested for Borrelia with an enzyme-linked immunosorbent assay were positive. Lichen sclerosus et atrophicus and morphea have previously been reported to be possibly related to Borrelia infection. We postulate that a similar relationship to Borrelia infection may be true for ALDY implying that ALDY may be an early superficial stage of morphea.